2012
DOI: 10.1080/10509674.2011.650349
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profiles of Intimate Partner Violence Offenders With and Without PTSD

Abstract: Intimate partner violence (IPV) is a serious forensic and clinicalproblem throughout the United States. Research aimed at defining and differentiating subgroups of IPV offenders using standardized personality instruments may eventually help with matching treatments to specific individuals to reduce recidivism. The current study used a convenience sample of court-ordered IPV offenders to explore whether the presence of posttraumatic stress disorder (PTSD) can reliably differentiate this population in terms of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…However, an emerging literature recasts these childhood experiences as traumatic stress exposures. Using broader assessments of traumatic stress, clinical studies indicate that 75%-90% of male IPV perpetrators report exposure to one or more event that would meet Diagnostic and Statistical Manual (DSM) definition of trauma exposure (Criterion A for the diagnosis of PTSD; Hoyt, Wray, Wiggins, Gerstle, & Maclean, 2012;Maguire et al, 2015;Semiatin, Torres, LaMotte, Portnoy, & Murphy, in press). In addition, military veterans with PTSD have rates of partner violence that are about 3 times higher than the rates observed among veterans without PTSD (Taft, Watkins, Stafford, Street, & Monson, 2011).…”
Section: Models That Integrate Risk Assessment and Risk Management Wimentioning
confidence: 99%
“…However, an emerging literature recasts these childhood experiences as traumatic stress exposures. Using broader assessments of traumatic stress, clinical studies indicate that 75%-90% of male IPV perpetrators report exposure to one or more event that would meet Diagnostic and Statistical Manual (DSM) definition of trauma exposure (Criterion A for the diagnosis of PTSD; Hoyt, Wray, Wiggins, Gerstle, & Maclean, 2012;Maguire et al, 2015;Semiatin, Torres, LaMotte, Portnoy, & Murphy, in press). In addition, military veterans with PTSD have rates of partner violence that are about 3 times higher than the rates observed among veterans without PTSD (Taft, Watkins, Stafford, Street, & Monson, 2011).…”
Section: Models That Integrate Risk Assessment and Risk Management Wimentioning
confidence: 99%
“…Of particular interest are mandated patients. These individuals may have significant levels of posttraumatic stress symptoms (Hoyt, Wray, Wiggins, Gerstle, & Maclean, 2012), as well as disturbances in self-organization, given their history of chronic exposure to traumatic events in childhood. However, because they tend not to seek help for traumatic distress, they are rarely studied in relation to CPTSD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that these men have usually experienced traumatic events at a greater frequency than other men in the community (Maguire et al, 2015), specifically exposure to violence by their parents (Delsol & Margolin, 2004). They also experience PTSD at higher rates than do community samples (Delsol & Margolin, 2004;Hoyt et al, 2012). Nevertheless, they have rarely been the subjects of studies in this area because they generally tend not to seek help for their traumatic distress.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this aspect, studies conducted in Israel have shown that Arab women reported a greater sense of danger than did Jewish women (Al-Krenawi, 1999; Morrison, 2004; Rabin, Markus, & Voghera, 1999). And, in terms of the mental health of the attacker, in studies of a population of men who were treated with court-mandated interventions for domestic violence, rates of mental distress among these men were found to be up to 3 times as high as they were in the general population (Askeland & Heir, 2014; Dutton, 1995; Hoyt, Wray, Wiggins, Gerstle, & Maclean, 2012; Rosenbaum & Leisring, 2003; Shorey, Febres, Brasfield, & Stuart, 2012).…”
Section: Sense Of Danger and Mental State Of The Attackermentioning
confidence: 99%